IMPLEMENTATION OF CHARACTER EDUCATION IN ENGLISH LANGUAGE LEARNING FOR JUNIOR HIGH SCHOOL - Madya Giri Aditama; Rhizki Amelia; Hikmah Pravitasari (Institut Pendidikan Tapanuli Selatan, 2022)
This study describes the implementation of character education in English language learning, including planning, implementation, and assessment. This research is observational studies research with a qualitative approach. The results obtained in this study are that character education in learning English at SMP Negeri 1 Limpung has been carried out both in planning, implementing, and assessing learning. At the learning planning stage, the teacher has entered the character values that will be applied in learning in the syllabus and lesson plans. The implementation character education through “Profil Pelajar Pancasila” which are noble character, global diversity, independence, mutual cooperation, critical reasoning, and creativity were implemented in the learning process. Assessment of english learning includes effective assessment.